Synergistic effects of niobium oxide–niobium carbide–reduced graphene oxide modified electrode for vanadium redox flow battery - Liu, Ting-Ruei; Chang, Yu-Chung; Bayeh, Anteneh Wodaje; Wang, Kai-Chin; Chen, Hsueh-Yu; Wang, Yao-Ming; Chiang, Tai-Chin; Tang, Mau-Tsu; Tseng, Shao-Chin; Huang, Hsin-Chih; Wang, Chen-Hao (Journal of Power Sources, 2020)
A powerful, low-cost niobium oxide–niobium carbide–graphene oxide (NbO2/NbC/rGO) hybrid electrocatalyst is prepared by refluxing, hydrothermal method, followed by annealing process at the optimum temperature of 1050 °C for all vanadium redox flow battery (VRFB) application. The NbO2/NbC/rGO electrocatalyst shows the best electrochemical activity with the highest peak current densities and the lowest peak differences toward VO2+/VO2+ and V2+/V3+ redox reactions from the cyclic voltammetry compared to other samples. The rate performance of VRFB cell using NbO2/NbC/rGO modified graphite felts (NbO2/NbC/rGO/GF) shows the voltage efficiencies of 89.3%, 81.7%, 71.0%, and 59.3% by the charge-discharge current densities of 40 mA cm−2, 80 mA cm−2, 120 mA cm−2, and 160 mA cm−2, respectively, which these performances are superior to those using the pretreated GFs and the untreated GF. The charge-discharge stability test of the VRFB cell using NbO2/NbC/rGO/GF demonstrates no significant decay after 100 cycles by the current density of 80 mA cm−2. This observation is due to the synergistic effects related to the presence of excess oxygen vacancies on NbO2/NbC, the high content of oxygen functional groups, and the high electrical conductivity characteristics of the graphene sheet. [Display omitted] •This work is the first demonstration of NbO2/NbC/rGO as a hybrid electrocatalyst for the VRFB.•NbO2/NbC/rGO shows a significant synergistic effect which can enhance the charge-discharge efficiency.•VRFB using NbO2/NbC/rGO shows no significant decay after 100 charge-discharge cycles.